Determinants of Indonesian Consumer’s Intention to Purchase Halal Food in Overseas: Modified Theory Planned Behavior Model with Religiosity - Destiana, Aulia R; Tairas, David R (UI Scholars Hub, 2021)
This study aimed to find the relationship between the intentions of Indonesian consumers in buying Halal food products abroad as a dependent variable with components in the Theory of Planned Behavior (TPB) namely attitudes, subjective norms, perceived behavioural control modified with religious relations as an independent variable. This research is a combination of research previously conducted by Alam and Sayuti (2011) and Mukhtar and Butt (2012). This study expands the theory by combining the variables used in previous research conducted by Alam and Sayuti (2011), the use of the TPB theory in halal food purchasing in Malaysia and Mukhtar and Butt's (2012) research, the role of religiosity in the intention to choose halal products. Thus, this study contributes to broadens the understanding of the determinants that affect the reasons of Indonesian Muslim consumers purchase halal food in overseas. From a tourism point of view, the finding also provide support for investments decision in halal food supply chain for instance food producers or suppliers in non-Indonesian countries consider the potential of Indonesian Muslim consumers. This study uses qualitative and quantitative methods. Data collection method is done by distributing the questionnaire online with the nonprobability convenience sampling method. Responding to 201 respondents with the criteria Indonesian citizen who have travel abroad at least once. In processing the respondent’s data, this study uses SPPS. The findings of this study indicate subjective norm, perceived behavioural control, and intra-personal religiosity have a positive and significant influence on the intentions of Indonesian consumers in purchasing Halal food products in overseas. Meanwhile, attitude and interpersonal religiosity not significant in explaining the intention of Indonesian consumers in buying Halal food products in overseas.